The Role of KH. Mukmin in the Spread of Islam in Gedangan, Sidoarjo in 1904 - Adhimah, Himmatin; Syaifullah, Ahmad Rizqi; Wibowo, Wahyu Adi (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to examine the role of KH. Mukmin in the spread of Islam in Sidoarjo in 1904. The main focus of the research is to understand KH. Hasan Mukmin’s contributions to the dissemination of Islam in Sidoarjo, to explore his role as a successor or teacher of the Qadiriyah-Naqshbandiyah Sufi order, and to identify the challenges he faced during the Gedangan uprising of 1904. This study uses library research methods by referring to books about KH. Mukmin, articles, journals, and other related documents.The findings show that KH. Hasan Mukmin was the only son of a religious scholar from Yogyakarta. His father was a leader of the Qadiriyah-Naqshbandiyah order, which is a combination of two major Sufi paths: Qadiriyah and Naqshbandiyah. In addition to studying, KH. Mukmin also sold woven mats and worked as a healer. He delved into mystical knowledge within the Qadiriyah-Naqshbandiyah order, which allowed him to master spiritual invulnerability and esoteric powers. Due to these abilities, he became well-known and had many students and followers.The 1904 Gedangan riot is a significant historical event worth discussing. The naming of KH. Mukmin Street is a form of recognition from the government for Kassan Moekmin, the figure behind the Gedangan uprising of 1904.